ANALYZE MULTIPLE CHOICE ITEMS USING PHP PROGRAMMING LANGUAGE - Cahyana, Yana; Faisal, Sutan; Heryono, Heri (International Journal of Psychosocial Rehabilitation, 2020)
High School is one of the High Schools in the Indonesian national education system. Students must be more intense in the learning process in order to get opportunities to the Higher Education level as expected, for that teachers must provide more precise and effective teaching. The purpose of this study is to build applications using the PHP programming language so as to facilitate teachers in analyzing multiple choice items quickly and accurately. This research methodology is based on the results of the analysis of the research model that will be used, the results of the selection of the development of the system is used the Waterfall model. The results of this study are to build applications using the PHP programming language making it easier for teachers to analyze the items quickly and accurately.